Vesiculation of Rhyolitic Melts Under Oscillatory Pressure - Seropian, Gilles; Kennedy, Ben M.; Kendrick, Jackie E.; Lavallée, Yan; Nichols, Alexander R. L.; von Aulock, Felix W.; Dingwell, Donald B.; Hess, Kai-Uwe; Lamur, Anthony; Schauroth, Jenny; Vasseur, Jérémie; Wadsworth, Fabian B. (Frontiers in Earth Science, 2022)
Magma ascending in the Earth’s crust can undergo oscillations in pressure, from ultra-low frequency changes associated with tectonics, to relatively higher frequency oscillations associated with seismicity. Seismic waves travelling through shallow magma bodies can lead to a range of unrest phenomena and potentially trigger volcanic eruptions. The underlying mechanisms by which pressure oscillations can induce unrest or eruption remain debated. Here, we experimentally impose pressure oscillations on magma and study how they affect vesiculation processes. We use cylindrical samples (4.00 mm long, 4.85 mm diameter) of hydrous rhyolitic obsidian (0.11 ± 0.01 wt.% H2O) placed in alumina (AL23) crucibles and vary pressure by the uniaxial loading of an alumina plunger in a thermo-mechanical analyzer. We monitor vesiculation at temperatures of 950-990°C and confining pressure of 177 kPa. We perform two types of experiment: (1) “static” experiments (at constant pressure) and (2) “oscillating” experiments in which we impose sinusoidal pressure oscillations of up to 71 kPa upon the static pressure (i.e. between 106 and 250 kPa). In both cases, we dilatometrically observe sample expansion driven by vesiculation. Post-experimental bubble textures reveal that bubbles formed preferentially at the sample margins. For the oscillating experiments, the sample expansion rate is lower than in the static experiments, and there are fewer vesicles at the sample margins. We examine the constituent processes of bubble formation (nucleation, growth, coalescence) and gas loss (diffusion, permeable flow) occurring during static experiments and with the added element of pressure oscillations. The most likely mechanism responsible for reduced sample expansion is that pressure oscillations drive the sample in and out of water saturation conditions and thus reduce the fraction of residence time over which bubble nucleation and/or growth are driven. Future work will be needed to confirm this hypothesis. These results are relevant to the study of earthquake-volcano interactions, where a magma body sits close to volatile saturation is subject to pressure fluctuations.